Intermolecular interactions and structural organization of a native chitin-chitosan hydrocolloid network resolved by solid-state NMR and molecular dynamics - Qinghui Cheng; Chunyan Lu; Xiufang Gong; Qingyan Wang; Siming Liao; Lihua Chen (Food Hydrocolloids, 2026)

Data-driven investigation of ship fuel consumption integrating causal inference and hierarchical analysis - Wenjie Cao; Xinjian Wang; Wei Zhang; Huanhuan Li; Siming Fang; Zaili Yang (Transportation Research Part D: Transport and Environment, 2026)

Ultrasound-assisted complexation of Millettia speciosa by-product protein with polyphenols: improved structural properties, antioxidant and hypoglycemic activities, and gut microbiota modulation - Meng Wang; Jiexi Li; Feng Li; Yebao Chen; Fangfang Ban; Hua Yang; Siming Zhu; Dan Xu; Junlin Wu (Food Chemistry, 2026)

MPM-DEM simulation of woody debris flow interaction with slit-check dams - Liu Ming; Xiaoqin Lei; Xinpo Li; Siming He; Xiaojun Guo; Liangliang Wang (Journal of Hydrology, 2026)

Stability of oil bodies under pulsed electric field exposure to rapeseed: New insights into improving oil extraction capacity - Qiqi Zhang; Jinling Hu; Yunyun Li; Bo Wang; Jing Wang; Jie Zhao; Siming Zhao; Caihua Jia; Jie Kuai; Guangsheng Zhou (Food Chemistry, 2026)

Comprehensive Transcriptomic and Proteomic Profiling of CILD40 with Novel Compound Heterozygous Mutations of DNAH9 - Siming Kong; Mingshuo Wang; Xuedong Wang; Yakun Liu; Pengfei Wang; Wenyan Song; Ziye Chen; Yuxin Su; Canhong Xiang; Yunfang Wang; Hui Bai (Phenomics, 2026)
Primary ciliary dyskinesia (PCD) is a rare genetic disorder characterized by impaired ciliary motility that leads to respiratory symptoms, laterality defects, and other systemic abnormalities. Despite significant advancements in genetic research identifying over 50 causative genes and enabling genetic diagnosis in approximately 90% of cases, comprehensive phenotypic characterization remains underexplored. We investigated two respiratory asymptomatic individuals (sisters) who exhibited laterality defects in a three-generation family, both of whom harbored novel compound heterozygous mutations (NM_001372.4:c.308del and NM_001372.4:c.11845G > A) in the dynein axonemal heavy chain 9 ( DNAH9 ) gene associated with primary ciliary dyskinesia-40 (CILD40). Structural modeling and western blotting analysis of HEK-293T cells demonstrated that the frameshift mutation abolished DNAH9 stability, whereas the missense mutation disrupted hydrogen bonds, leading to partial protein destabilization. Peripheral blood RNA sequencing revealed extensive dysregulation of axonemal and intraflagellar transport genes, implicating defects in microtubule-based motility in the two affected siblings with biallelic DNAH9 mutations, but not in their heterozygous family members or one unaffected relative. Plasma proteomic analysis of patients with CILD40 identified significant enrichment of pathways related to platelet activation, complement and coagulation cascades. Further comparative analysis with a patient with PCD caused by a CCDC40 mutation (CILD15 subtype) revealed differential signatures in CILD40, highlighting the potential of plasma proteomics for understanding distinct pathogenic mechanisms across PCD subtypes. These findings underscore the critical role of DNAH9 compound heterozygous mutations in CILD40 and provide new insights into the genetic, transcriptional, and proteomic phenotypic heterogeneity of PCD.

Plant-derived CTLA-4-targeting miR152 via lipid nanoparticles potentiates doxorubicin efficacy in breast cancer immunochemotherapy - Hanyi Ye; Wei Jin; Yifan Feng; Ze Wu; Shuhui Sun; Mengyao Cui; Shun Lv; Bing Jin; Chang Liu; Siming Wang; Ying Li; Zhengqi Dong (Science China Life Sciences, 2026)

Illumination-induced restructuring of extracellular polymeric substances from Klebsiella Sp. HDJY-1 drives indirect photodegradation of thifensulfuron-methyl - Jiaying Gu; Yaqi Jiao; Chunnan Zhou; Junxin Jia; Siming Li; Kai Wang; Hui Li; Hongtao Shi; Qin Zhou; Rong Liu; Li Li (Water Research, 2026)

Increased microbiological risks caused by extreme precipitation in a drinking water system in mountainous area: From source to tap - Xinyan Xiao; Chen Cheng; Xiuxiu Wang; Ziqi Luo; Lihua Li; Siming Hu; Dongmei Zhu; Mingbao Feng; Chengsong Ye; Xin Yu (Journal of Hazardous Materials, 2026)

Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics” [Food Chem. 513 (2026) 149020] - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Changes in ginseng wine flavor characteristics during fermentation with Saccharomyces cerevisiae - Shen Yao; Yang Li; Xianwei Zeng; Yuan Cui; Zhaolian Li; Meichen Liu; Daqing Zhao; Shiting Yu; Siming Wang (Food Chemistry, 2026)

Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Screening and characterization of microbial consortia for biodegradation of high-salt and high-oil food waste - Meng Wang; Lirong Xia; Minghui Yang; Hua Yang; Zhongsheng Tang; Yebao Chen; Siming Zhu; Junlin Wu (Waste Disposal & Sustainable Energy, 2026)

Non-thermal processing of Citrus reticulata cv. Chachiensis pulp: Antioxidant screening and mechanism in Caenorhabditis elegans based on transcriptomics and metabolomics - Quancen Lee; Siming Zhu; Ping Chen; Yutao Wang; Liang Chen; Zhendong Wang (Food Bioscience, 2026)

Efficient simulation of landslide-induced surges and control effects of different position piles based on an improved flow-flow model - Zhangqing Wang; Yong Wu; Yongjie Zhao; Yingpeng Wang; Siming He; Xinpo Li; Lei Zhu (Journal of Hydrology, 2026)

Fragmentation induced mobility and runout mechanism of large rock avalanche: A case study on the Tibetan Plateau, China - Xiong Tang; Lei Zhu; Siming He; Michel Jaboyedoff; Zenan Huo; Running Hou; Di Wang; Yu Luo (Engineering Geology, 2026)

Synergistic control of Pseudomonas aeruginosa by LAB and phage for sustainable aquatic preservation - Siming Xue; Kairui Zhao; Rui Dong; Haichen Li; Ruizi Wang; Wei Cheng; Yuqi Fan; Qin Zhang; Ziyi Xue; Yujin Wu; Jun Zhang; Yanmei Sun; et al. (Food Bioscience, 2026)

Based on sensory evaluation, E-nose, and GC-IMS analysis of volatile component differences in various kinds of sheep fats - Yaping Wang; Xiaolei Tang; Xitong Yuan; Hanying Xu; Yuxi Liu; Yaling Yang; Zhihui Lin; Siming Wang; Bin Qi; Li Liu (Natural Product Research, 2026)

Berberine inhibits ISG15 and pyroptosis to attenuate diabetic kidney disease inflammation and fibrosis - Lingzhi Huang; Qinqin Chen; Xiaoxiao Liu; Liuqing Wang; Xingyue Liao; Siming Yuan; Liqin Tang (Apoptosis, 2026)

Purifying or polluting? Tracing membrane-based microplastics release for long-term drinking water safety - Shunyao Yu; Siming Xie; Yaya Zhu; Wei Wang; Zhitong Liu; Xian Bao; Jun Ma (Water Research, 2026)

Optimization on escape exit selection for personnel in highway tunnel fires - Jinghong Wang; Jintao Li; Hongcheng Lu; Siming Wang; Ran Ye; Jialin Wu (Tunnelling and Underground Space Technology, 2026)

A machine learning hybrid model for heat transfer per meter prediction of energy pipe pile - Siming Dong; Chenglong Wang; Hanlong Liu; Abdelmalek Bouazza; Xuanming Ding; Gangqiang Kong (Geothermics, 2026)

Ultrasonic-enzymatic synergistic extraction of Ophiopogon japonicus polysaccharides: Structural characterization, in vitro hypoglycemic activity, and regulatory mechanism on human gut microbiota - Junlin Wu; Meng Wang; Yutong Liao; Sijie Huang; Xincheng Ye; Fengchuan Ma; Siming Zhu; Yunping Peng; Dan Xu (Food Bioscience, 2026)

Okadaic acid induces oxidative stress and immunotoxicity in zebrafish: involvement of the p53 pathway and behavioral alterations - Duo Chen; Siming Pan; Jiapeng Wang; Zhenlu Li; Chenhuan Dong; Yuanxin Liang; Yilin Huang; Youqiang Chen; Ting Xue; Chentao Lin (Fish & Shellfish Immunology, 2026)

Numerical study on the damage evaluation of a check dam under boulder-enriched debris flow impact - Wei Liu; Shuaixing Yan; Siming He; Dongpo Wang (Engineering Geology, 2026)

Microbial electrochemical reduction of chromate in groundwater driven by Thiobacillus denitrificans - Luyao Wang; Siming Chen; Song Wang; Xinxin Li; Baogang Zhang (Journal of Environmental Chemical Engineering, 2025)

Cellulose-engineered janus periosteum with compartmentalized angiogenic and osteo-immunomodulatory abilities for bone regeneration - Wuyan Xu; Kun Liu; Jiaqing Chen; Junliang Liu; Siming Li; Hua Wang; Binghong Luo; Qingqi Meng (Carbohydrate Polymers, 2025)

Methionine in embryonic development: metabolism, redox homeostasis, epigenetic modification and signaling pathway - Chang Yan; Biyan He; Chenjun Wang; Wanzhen Li; Siming Tao; Jingqing Chen; Yuquan Wang; Ling Yang; Yingjie Wu; Zhenlong Wu; Ning Liu; Yinghe Qin (Critical Reviews in Food Science and Nutrition, 2025)

High-performance dynamic radiative regulation via controllable macroscopic materials modulation - Ya Huang; Xueke Wu; Siming Zhao; Baoshun Wang; Zhuojing Zhao; Di Gao; Run Li; Yunrui Li; Fei Wang; Fan Lan; Yanlong Zhao; Rufan Zhang (Science Bulletin, 2025)

A hierarchical conflict resolution strategy for collision avoidance in multi-ship encounter scenarios - Ni Shengke; Xian Guoliang; Zhao Zhijie; Wang Xinjian; Liu Guangqiang; Fan Yaxin; Fang Siming (Ocean Engineering, 2025)

Interaction mechanism and structure-activity relationship of hesperidin, methyl hesperidin and hesperidin methyl chalcone with ovalbumin: A comparative study - Xuefei Wen; Xinpeng Li; Siming Zhu; Liang Chen; Zhendong Wang; Ming Yu; Zhanhua Deng (Food Chemistry, 2025)

Complexes of Dendrobium officinale anthocyanins and polysaccharides: Structural characteristics, stability, antioxidant properties, and bioavailability - Bowen Sui; Yanling Sun; Jingzhi Wang; Yuan Cui; Haibo Xu; Daqing Zhao; Meichen Liu; Zhengqi Dong; Siming Wang; Shichao Liu (Food Bioscience, 2025)

A galacturonan from sea buckthorn (Hippophae rhamnoides L.) berry modulates dyslipidemia by promoting hepatic lipolysis and mitochondrial oxidation - Yunpeng Sun; Weifeng Ni; Dongyi Wang; Jixiang Ren; Daqing Zhao; Shiting Yu; Shichao Liu; Shaojie Zhang; Siming Wang; Weinan Wang; Meichen Liu (Carbohydrate Polymers, 2025)

Bibliometric and visual analysis of drug-specific immunotherapy from 1990 to 2024 - Zhengjiu Cui; Xiaorui Chen; Siming Zhai; Yuanyuan Wang; Chanchan Hu; Bin Yuan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Novel metabolic pathways of bioelectrochemical vanadate reduction by Thiobacillus denitrificans without exogenous electron donor supplementation in groundwater - Luyao Wang; Siming Chen; Rui Li; Baogang Zhang (Water Research, 2025)

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

Study on the influence of 3D pre-existing joint on rockfall fragmentation during impact based on discrete element method - Yongjie Zhao; Yong Wu; Yingpeng Wang; Siming He; Xinpo Li; Lei Zhu; Zhangqing Wang (Computers and Geotechnics, 2025)

Decreasing the pH value would improve the swallowing characteristics of whey protein isolate-enriched thickened fluids for dysphagia populations - Zihang Cheng; Kedu Wang; Dongling Qiao; Bowen Li; Siming Zhao; Binjia Zhang (Food Research International, 2025)

Catalytic-difference elucidating of hesperidin and naringin by Rhamnosidase and prunin production enhancing through enzyme mutation - Xinpeng Li; Ping Chen; Lin Chen; Sheng Gao; Zhendong Wang; Siming Zhu (Food Bioscience, 2025)

An integrated non-alkaline derivatization strategy using 2,2′-dithiodipyridine and HPLC for simultaneous analysis of total and low-molecular-weight free thiols in human serum - Zhiyu Shao; Jie Zeng; Jun Dong; Fusui Ji; Hongxia Li; Ruiyue Yang; Wenxiang Chen; Wenyu Li; Siming Wang (Analytica Chimica Acta, 2025)

Encapsulated benzoic acid alleviated LPS-induced intestinal damage via NRF2 activation - Yanyan Zhang; Tianjiao Wang; Qing He; Mahmoud M. Abouelfetouh; Qin Fu; Siming Yao; Shiqiang Ju; Zhenlei Zhou; Qiao Li (Food Bioscience, 2025)

Discovery of potent MD2 inhibitors by hierarchical virtual screening strategy and bioactivity evaluation - Lili Yang; Jialu Liu; Lei Di; Siming Tang; Ping Hu; Fang Wang; Zeng Li (Chemico-Biological Interactions, 2025)

Genetic analysis and fine mapping reveal that AhRt3, which encodes an anthocyanin reductase, is responsible for red testa in cultivated peanuts - Yanyan Tang; Xiantao Zhou; Xin Li; Cai Zhou; Wenlin Wang; Mo Zhou; Zhicheng Hu; Xiaobei Li; Kaiyuan Zhang; Siming Wang; Zhihao Zhang; Hao Chen; et al. (Theoretical and Applied Genetics, 2025)

Isolation and identification of native microalgae from the Yellow River Delta: A dual-focus study on the tolerance assessment of microalgae and their growth enhancement on Sesbania cannabina under saline-alkali stress - Xiao Yu; Siming Li; Jiahao Liang; Shenkun Liu; Yinchu Wang; Jianchao Yang; Chenggang Ren; Chunli Ji; Hongli Cui; Song Qin (Algal Research, 2025)

Review of Research Progress on the Impact of Submarine Groundwater Discharge on Pockmark Formation and Evolution - Zhengrong Zhang; Hongxian Shan; Xuezhi Feng; Zhentian Jia; Long Jiang; Siming Wang; Chaoqi Zhu (Journal of Marine Science and Engineering, 2025)
Pockmarks are globally distributed geomorphic features exhibiting diverse morphologies. Their geometric characteristics are commonly quantified by the radius-to-depth ratio. The evolutionary process of these features typically follows a cyclical pattern comprising initiation, expansion, stabilization, and decline. Submarine groundwater discharge (SGD), a seasonally modulated land–sea exchange process, exerts a significant influence on the formation and evolution of pockmarks. This influence is mediated through hydrodynamic forcing effects, sediment redistribution, and coupled chemical–biological interactions. This review systematically examines the formation mechanisms, evolutionary patterns, and primary controlling factors of pockmarks induced by SGD. It integrates recent research developments and global case studies to elucidate the dynamic interplay of multiple influencing factors. This study emphasizes the significance of interdisciplinary approaches in marine geological research and identifies key areas for future investigation. These insights aim to enhance risk assessment frameworks for marine hazards and inform marine spatial planning strategies.

Polysaccharide–dextrin thickened fluids for individuals with dysphagia: recent advances in flow behaviors and swallowing assessment methods - Kedu Wang; Zihang Cheng; Dongling Qiao; Fengwei Xie; Siming Zhao; Binjia Zhang (Critical Reviews in Food Science and Nutrition, 2025)

Artificial intelligence in plastic recycling and conversion: A review - Yi Fang; Yuming Wen; Leilei Dai; Chi-Hwa Wang; Siming You; Wangliang Li (Resources, Conservation and Recycling, 2025)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

Review of Research Progress on the Influence of Groundwater Discharge on Seabed Stability - Zhentian Jia; Hongxian Shan; Hanlu Liu; Zhengrong Zhang; Long Jiang; Siming Wang; Yonggang Jia; Yongzheng Quan (Journal of Marine Science and Engineering, 2025)
Submarine groundwater discharge (SGD) refers to the flow of groundwater that enters seawater through the seabed surface at the edge of the coastal shelf. During this discharge process, seepage and initiation can easily trigger seabed instability, which significantly influences the breeding, occurrence, and evolution of marine geological events. The narrow distribution of land near the coastline and the substantial flux of groundwater discharge are closely associated with typical seabed geological events, such as submarine landslides and collapse pits, which are prevalent in the sea area. This paper analyzes the current research status of SGD both domestically and internationally, elucidates the interaction mechanisms between groundwater discharge and the seabed, and integrates existing studies on discharge-induced slope instability, collapse pit formation, and seabed erosion and resuspension. It summarizes and evaluates the existing research on the influence of seabed groundwater discharge on the evolution of seabed geological structures, identifies key scientific problems that urgently need to be addressed, and proposes future research directions that require further emphasis. Additionally, the paper conducts research on the mechanisms by which groundwater discharge affects seabed stability, providing valuable insights for the study of coastal zones in China. It also offers a scientific basis for enhancing the understanding of the generation mechanisms of marine geological events and improving the technological capabilities for their prevention and control.

The impact of school activity space layout on children's physical activity levels during recess: An agent -based model computational approach - Jiameng Cui; Xue Meng; Siming Qi; Junwen Fan; Wenxuan Yu; Hongxing Liu; Xiang Wang; Yu Zhang (Building and Environment, 2025)

Conformational adjustment of 1,2-rhamnosyltransferase by prepeptides: Experimental and dynamic analysis - Chunqing Wang; Siming Zhu (Food Bioscience, 2025)

Evaluating the wilderness status of long-distance trails in the United States - Exploring the potential of SDGSAT-1 glimmer imager data - Liding Wang; Mingyang Lv; Changyong Dou; Yue Cao; Steve Carver; Xiancai Lu; Shaochun Dong; Siming Deng; Huadong Guo (Remote Sensing of Environment, 2025)

Analysis of sediment re-formation factors after ginseng beverage clarification based on XGBoost machine learning algorithm - Jiabao Feng; Yuan Cui; Chunyan Jiang; Xueyuan Bai; Daqing Zhao; Meichen Liu; Zhengqi Dong; Shiting Yu; Siming Wang (Food Chemistry, 2025)

Experimental Investigation of Seismic Signal Characteristics Arising from Basal Stress Fluctuations in Granular Flow - Xiao Yu; Zheng Chen; Siming He; Wei Liu; Dongpo Wang (Rock Mechanics and Rock Engineering, 2025)

Characteristics of Dissolved Inorganic Carbon (DIC) in the Western Coast of the Taiwan Strait Using a Shipboard Measurement - Jiehua Hu; Jinpei Yan; Hang Yang; Siming Huang; Siying Dai; Xiaoke Zhang; Shanshan Wang; Shuhui Zhao (Journal of Marine Science and Engineering, 2024)
An online dissolved inorganic carbon (DIC) monitoring system was produced to achieve high spatial and temporal resolution in DIC data from the western Taiwan Strait (WTS) during the summer. Surface seawater DIC, salinity, dissolved organic carbon (DOC), Chl-a, and NO3− samples were collected, as well as the vertical profiles of DIC, to understand DIC variations in the WTS. The results showed that the range of DIC levels in the surface seawater from the WTS was from 1.68 to 2.21 mmol/L (Mmol), with an average of 1.93 ± 0.19 Mmol, which was consistent with the sampling results using titration determination, with an average of 1.98 ± 0.12 Mmol. A high correlation (R2 = 0.96) was presented between the online monitoring and sampling detection of DIC, indicating that DIC could be measured with high accuracy using the online monitoring system. The spatial distribution of DIC was similar to that of salinity, but it was different from that of DOC and Chl-a. The DIC concentration positively correlated with salinity (R2 = 0.51) and presented a negative correlation (R2 = 0.92) with seawater temperature. However, the surface seawater DIC was almost independent from DOC and Chl-a in the observation sea areas. The DIC levels first increased and then decreased with the depth, with the highest DIC concentration occurring in the subsurface water at about 10 m, which was similar to the profiles of salinity and Chl-a in the northern and southern areas of the WTS. The profiles of DIC, salinity, NO3−, and Chl-a were almost independent from the water depth in the central WST. This indicated that seawater DIC in the WTS was mainly affected by seawater temperature, salinity, and the vertical mixing of sea water, but it was less impacted by TOC and Chl-a.

Microplastics alter the migration and transformation of vanadium in the riverine sediment environment - Siming Chen; Xinyue Zhang; Luyao Wang; Cuibai Chen; Jiamin Huang; Baogang Zhang (Science of The Total Environment, 2024)

Escherichia coli heat-labile enterotoxin B subunit as an adjuvant of mucosal immune combined with GCRV-II VP6 triggers innate immunity and enhances adaptive immune responses following oral vaccination of grass carp (Ctenopharyngodon idella) - Jiyuan Yin; Huiliang Wu; Wei Li; Yingying Wang; Yingying Li; Xubing Mo; Siming Li; Yan Ren; Houjun Pan; Peng Jiang; Qing Wang (Fish & Shellfish Immunology, 2024)

CO prodrugs: a new scaffold of adamantane-fused norbornen-7-ones with tunable water solubility - Ce Yang; Xingyue Ji; G. S. Sainaga Jyothi Vaskuri; Xiaoxiao Yang; Wen Lu; Zhengnan Yuan; Dongning Liu; Siming Wang; Chalet Tan; Binghe Wang (Medicinal Chemistry Research, 2024)

Advancements and future perspectives in the study of oligosaccharides derived from edible-medicinal mushrooms - Shuo Wang; Jiajie Qi; Xiaoming Cai; Weijie Wu; Zhuo A. Wang; Siming Jiao; Caihong Dong; Yi Li; Zhenquan Yang (Food Bioscience, 2024)

Experimental study on human evacuation onboard passenger ships considering heeling angle and opposite directions - Siming Fang; Zhengjiang Liu; Xinjian Wang; Ben Matellini; Jin Wang; Zaili Yang; Xinyu Zhang; Bo Wan; Shengke Ni (Ocean Engineering, 2024)

Comparison and inhibition mechanism study on the in vitro digestibility of rice starch complex with soy β-conglycinin and soy glycinin - Xin Shi; Xuxu Li; Ruifeng Wang; Meng Niu; Siming Zhao (Food Hydrocolloids, 2024)

Influence of group VIB metals introduced into zeolite on the adsorption performance of VOCs in cooking oil fumes - Honghong Yi; Siming Guo; Yuting Yuan; Qingjun Yu; Fengshi Meng; Wenjing Wu; Shunzheng Zhao; Ya Wang; Xiaolong Tang (Chemical Engineering Journal, 2024)

MPM simulation of frictional heating–induced hypermobility of landslides - Xiaoqin Lei; Siming He; Xiaoqing Chen; Zongji Yang; Youkou Dong; Liangliang Wang (Landslides, 2024)

Ronald T. Borchardt: a pioneer in drug discovery and development - Michael S. Wolfe; Xiangming Guan; Binghe Wang; Siming Wang (Medicinal Chemistry Research, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

Unveiling the inverse antimicrobial impact of a hetero-chitooligosaccharide on Candida tropicalis growth and biofilm formation - Yangyang Liu; Ruilian Li; Yuchen Zhang; Siming Jiao; Tong Xu; Yuhang Zhou; Yujing Wang; Jinhua Wei; Wei Du; Morihisa Fujita; Yuguang Du; Zhuo A. Wang (Carbohydrate Polymers, 2024)

Corrigendum to “Necroptosis and NLPR3 inflammasome activation mediated by ROS/JNK pathway participate in AlCl3-induced kidney damage” [Food Chem. Toxicol. 178 (2023) 113915] - Jiayu Du; Xuliang Zhang; Jian Zhang; Siming Huo; Bo Li; Qi Wang; Miao Song; Bing Shao; Yanfei Li (Food and Chemical Toxicology, 2024)

A numerical method to consider the interaction between multiple fractures in frozen rocks based on XFEM - Yun Zhou; Xianjun Tan; Diansen Yang; Weizhong Chen; Zhouzhou Su; Peichao Zheng; Reziwanguli Shataer; Dong Wang; Siming Tian; Wei Wang (Computers and Geotechnics, 2024)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

A unified model for frost wedging in an open fissure under unidirectional freezing - Peichao Zheng; Xianjun Tan; Hailiang Jia; Kai Shen; Zhouzhou Su; Yun Zhou; Reziwanguli Shataer; Yi Xie; Dong Wang; Siming Tian; Wei Wang; Weizhong Chen (International Journal of Rock Mechanics and Mining Sciences, 2024)

Oral immunization with recombinant L. lactis expressing GCRV-II VP4 produces protection against grass carp reovirus infection - Huiliang Wu; Jiyuan Yin; Siming Li; Hao Wang; Peng Jiang; Pengfei Li; Zhaoyang Ding; Han Yan; Bo Chen; Linchuan Wang; Qing Wang (Fish & Shellfish Immunology, 2024)

Blocking-baffle mechanism of vegetation to rock avalanche on the forested slope of the east Sichuan-Tibet Mountains - Yong Wu; Zhang-qing Wang; Xin-po Li; Siming He; Xiao-qin Lei (Landslides, 2024)

Protective effect of retaining wall on rock avalanche: A case study of Nayong rock avalanche in China - Zhongfu Wang; Fengge Shi; Siming He; Xusheng Zhang; Jingying Wang; Enlong Liu (Journal of Mountain Science, 2024)

Incorporating edible oil during cooking tailors the microstructure and quality features of brown rice following heat moisture treatment - Yabin Guo; Ruolan Fang; Zhuoting Wu; Gaolei Xi; Dongling Qiao; Genfa Wang; Ting Cui; Liang Zhang; Siming Zhao; Binjia Zhang (Food Research International, 2024)

Assessing the Efficiency of Thermochemical Pressurization in the Jiweishan Rockslide - Yu Deng; Xuanmei Fan; Gianvito Scaringi; Dongpo Wang; Siming He (Rock Mechanics and Rock Engineering, 2024)

Effect of hydrophobic sucrose esters with different fat acid composition and esterification degree on whipped cream properties - Di Zeng; Yongjian Cai; Tongxun Liu; Lihua Huang; Junwei Wang; Mouming Zhao; Siming Zhu; Qiangzhong Zhao (Food Hydrocolloids, 2024)

Importance sampling-based probabilistic performance modeling of low-, mid- and high-strength pipelines under coupling effect of hydrogen-induced damage and corrosion - Yihuan Wang; Zhenwei Zhang; Siming Liu; Ailin Xia; Ruiling Li; Guojin Qin (Process Safety and Environmental Protection, 2023)

Enrichment of resistant starch in starch-protein hydrolysate binary matrix by modulating pH during thermal processing - Cuihong Dai; Zihang Cheng; Yanyu Chen; Dongling Qiao; Gaolei Xi; Qiuling Wang; Fan Zhu; Siming Zhao; Binjia Zhang (Food Research International, 2023)

A 26-week repeated dose toxicity evaluation of sporoderm-removed Ganoderma lucidum spores in rats - Lijuan Xia; Ruimin Sun; Liyan Zhang; Jinrong Li; Chengda Zhang; Qian Yang; Lili Zhang; Siming Zhang; Hanbo Wang; Hanying Lyu; Wanqiang Lyu; Zhenhao Li; et al. (Food and Chemical Toxicology, 2023)

Dibutyl phthalate induces liver fibrosis via p38MAPK/NF-κB/NLRP3-mediated pyroptosis - Siming Huo; Bo Li; Jiayu Du; Xuliang Zhang; Jian Zhang; Qi Wang; Miao Song; Yanfei Li (Science of The Total Environment, 2023)

Research progress on the adsorption of sulfocompounds in flue gas - Siming Guo; Qingjun Yu; Shunzheng Zhao; Xiaolong Tang; Ya Wang; Yiming Ma; Yuhan Long; Honghong Yi (Chemical Engineering Journal, 2023)

Role of mining waste trade on green development in China: Policy implications for circular economy - Siming Yu; Xun Wang; Jiaming Liu; Fang Wei (Resources Policy, 2023)

A quantitative study of the factors influencing human evacuation from ships - Siming Fang; Zhengjiang Liu; Xihan Yang; Xinjian Wang; Jin Wang; Zaili Yang (Ocean Engineering, 2023)

The impact of GmTSA and GmALS on soybean salt tolerance: uncovering the molecular landscape of amino acid and secondary metabolism pathways - Minghao Sun; Siming Wei; Jiarui Liu; Luyao Wang; Yu Zhang; Limin Hu; Jingxi Piao; Zhao Liang; Hongwei Jiang; Dawei Xin; Ying Zhao; Qingshan Chen; et al. (Theoretical and Applied Genetics, 2023)

Kif15 deficiency contributes to depression-like behavior in mice - Junpei Wang; Qifeng Tu; Siming Zhang; Xiaomei He; Chao Ma; Xiaowei Qian; Ronghua Wu; Xinyu Shi; Zhangyi Yang; Yan Liu; Zhangji Dong; Mei Liu (Metabolic Brain Disease, 2023)

Dibutyl phthalate causes heart damage by disrupting Ca2+ transfer from endoplasmic reticulum to mitochondria and triggering subsequent pyroptosis - Bo Li; Siming Huo; Jiayu Du; Xuliang Zhang; Jian Zhang; Qi Wang; Miao Song; Yanfei Li (Science of The Total Environment, 2023)

Degradation characteristics of intracellular and extracellular ARGs during aerobic composting of swine manure under enrofloxacin stress - Jiaojiao Xu; Jielan Huang; Longhai Chen; Majian Chen; Xin Wen; Pengfei Zhang; Siming Li; Baohua Ma; Yongde Zou; Yan Wang; Xindi Liao; Yinbao Wu (Chemical Engineering Journal, 2023)

Russia-Ukraine war perspective of natural resources extraction: A conflict with impact on sustainable development - Shouwen Wang; Lijie Xu; Siming Yu; Siyao Wang (Resources Policy, 2023)

Necroptosis and NLPR3 inflammasome activation mediated by ROS/JNK pathway participate in AlCl3-induced kidney damage - Jiayu Du; Xuliang Zhang; Jian Zhang; Siming Huo; Bo Li; Qi Wang; Miao Song; Bing Shao; Yanfei Li (Food and Chemical Toxicology, 2023)

Free-standing high-entropy alloy plate for efficient water oxidation catalysis: structure/composition evolution and implication of high-valence metals - Lingya Yi; Siming Xiao; Yunpeng Wei; Dazhi Li; Rongfei Wang; Shengfeng Guo; Weihua Hu (Chemical Engineering Journal, 2023)

Isoalantolactone relieves depression-like behaviors in mice after chronic social defeat stress via the gut-brain axis - Siming Wang; Qihan Cai; Lu Xu; Yanan Sun; Mengmeng Wang; Yu Wang; Lili Zhang; Keqing Li; Zhiyu Ni (Psychopharmacology, 2023)
Rationale The management of depression continues to be challenging despite the variety of available antidepressants. Herbal medicines are used in many cultures but lack stringent testing to understand their efficacy and mechanism of action. Isoalantolactone (LAT) from Elecampane ( Inula helenium ) improved the chronic social defeat stress (CSDS)-induced anhedonia-like phenotype in mice comparable to fluoxetine, a selective serotonin reuptake inhibitor (SSRI). Objectives Compare the effects of LAT and fluoxetine on depression-like behaviors in mice exposed to CSDS. Result The CSDS-induced decrease in protein expression of postsynaptic density (PSD95), brain derived neurotrophic factor (BDNF), and glutamate receptor subunit-1 (GluA1) in the prefrontal cortex was restored by LAT. LAT showed robust anti-inflammatory activity and can lessen the increase in IL-6 and TNF-α caused by CSDS. CSDS altered the gut microbiota at the taxonomic level, resulting in significant changes in α- and β-diversity. LAT treatment reestablished the bacterial abundance and diversity and increased the production of butyric acid in the gut that was inhibited by CSDS. The levels of butyric acid were negatively correlated with the abundance of Bacteroidetes , and positively correlated with those of Proteobacteria and Firmicutes across all treatment groups. Conclusions The current data suggest that, similar to fluoxetine, LAT show antidepressant-like effects in mice exposed to CSDS through the modulation of the gut-brain axis.

Effect of particle crushing– and thermally induced pressurization on rockslide mobility - Yu Deng; Xuanmei Fan; Gianvito Scaringi; Dongpo Wang; Siming He (Landslides, 2023)

Development of a HPLC-UV Method for the Separation and Quantification of Hesperidin, Neohesperidin, Neohesperidin Dihydrochalcone and Hesperetin - Lin Chen; Siming Zhu; Chunqing Wang; Liang Chen (Natural Product Research, 2023)

Aspergillus sp. R3, a new producer for cyclopyazonic acid, inhibits rice sheath blight fungus Rhizoctonia solani Kühn - Xiangyu Qin; Yuanhang Chang; Yao Wang; Jie Yang; Siming Nie; Na Guo; Jian Xu; Fengkun Cai; Chunjian Zhao; Yujie Fu (Physiological and Molecular Plant Pathology, 2023)

T-2 toxin inhibits osteoblastic differentiation and mineralization involving mutual regulation between Wnt signaling pathway and autophagy - Jian Zhang; Peiyan Wang; Miao Song; Xuliang Zhang; Siming Huo; Jiayu Du; Bo Li; Zheng Cao; Yanfei Li (Chemico-Biological Interactions, 2023)

Application of artificial step-pools in natural hazard mitigation - Kehan Huang; Wei Liu; Mengzhen Xu; Siming He; Yifei Cui; Zhaoyin Wang (CATENA, 2023)

Refined-JinQi-JiangTang tablet ameliorates hypertension through activation of FGF21/FGFR1 axis in fructose-fed rats - Siming Li; Xiaoling Li; Jing Fan; Xinhang Jia; Hemeng Wang; Fangxin Dong; Haoyang Mao; Chen Zhang; Wenfei Wang; Ye Jiang; Lijun Yan; Na Zhang (Journal of Natural Medicines, 2022)

A Fusion Approach for Suppression of Environmental Noise in Spread Spectrum Induced Polarization Data - Siming He; Jian Guan; Dachuan Chen; Hang Xu; Yi Wang (Pure and Applied Geophysics, 2021)

Fracture of rocks in the mountains of Southeast Tibet under hydrothermal conditions at different elevations - Yong Wu; Yongxiang Wang; Waisman Haim; Siming He; Xinpo Li (Bulletin of Engineering Geology and the Environment, 2020)

Design and optimisation of a protective device for bridge piers against debris flow impact - Shuaixing Yan; Siming He; Dongpo Wang; Yong Wu (Bulletin of Engineering Geology and the Environment, 2020)

Numerical assessment of the impeding effect of check dams in the Hongchun debris flow gully, Sichuan Province, China - Wei Shen; Dongpo Wang; Siming He; Tonglu Li (Bulletin of Engineering Geology and the Environment, 2020)

In honor of Professor Robert P. Hanzlik on the occasion of his retirement - Siming L. Wang; Longqin Hu; Binghe Wang (Medicinal Chemistry Research, 2020)

Characterization of a bifunctional alginate lyase as a new member of the polysaccharide lyase family 17 from a marine strain BP-2 - Guiyuan Huang; Shunhua Wen; Siming Liao; Qiaozhen Wang; Shihan Pan; Rongcan Zhang; Fu Lei; Wei Liao; Jie Feng; Shushi Huang (Biotechnology Letters, 2019)

Towards practical application of gasification: a critical review from syngas and biochar perspectives - Siming You; Yong Sik Ok; Daniel C. W. Tsang; Eilhann E. Kwon; Chi-Hwa Wang (Critical Reviews in Environmental Science and Technology, 2018)

Identification of novel miRNAs and their target genes in Eucalyptus grandis - Zheng Lin; Qingfen Li; Qi Yin; Jinyan Wang; Baolong Zhang; Siming Gan; Ai-Min Wu (Tree Genetics & Genomes, 2018)

Measuring and estimating the impact pressure of debris flows on bridge piers based on large-scale laboratory experiments - Dongpo Wang; Zheng Chen; Siming He; Yang Liu; Hao Tang (Landslides, 2018)

Numerical analysis of effect of baffle configuration on impact force exerted from rock avalanches - YuZhang Bi; YanJun Du; SiMing He; XinPo Sun; DongPo Wang; XinPo Li; Heng Liang; Yong Wu (Landslides, 2018)

Data assimilation method based on the constraints of confidence region - Yong Li; Siming Li; Yao Sheng; Luheng Wang (Advances in Atmospheric Sciences, 2018)

Molecular cloning, recombinant expression, and antifungal functional characterization of the lipid transfer protein from Panax ginseng - Kexin Cai; Jiawen Wang; Min Wang; Hui Zhang; Siming Wang; Yu Zhao (Biotechnology Letters, 2016)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

Artemisinin mimics calorie restriction to extend yeast lifespan via a dual-phase mode: a conclusion drawn from global transcriptome profiling - DaTing Wang; Ming Wu; SiMing Li; Qian Gao; QingPing Zeng (Science China Life Sciences, 2015)

Fibroblast growth factor (FGF21) protects mouse liver against d-galactose-induced oxidative stress and apoptosis via activating Nrf2 and PI3K/Akt pathways - Yinhang Yu; Fuliang Bai; Yaonan Liu; Yongbi Yang; Qingyan Yuan; Dehua Zou; Susu Qu; Guiyou Tian; Liying Song; Tong Zhang; Siming Li; YunYe Liu; et al. (Molecular and Cellular Biochemistry, 2015)

A new acorane sesquiterpene from the aerial parts of Psychotria yunnanensis - Qinpei Lu; Junsong Wang; Jun Luo; Xiaobing Wang; Siming Shan; Lingyi Kong (Natural Product Research, 2014)

Comparative analysis of differentially expressed genes in Sika deer antler at different stages - Yu Zhao; Baojin Yao; Mei Zhang; Siming Wang; Hui Zhang; Wei Xiao (Molecular Biology Reports, 2013)

Erratum to: Xeno-repopulation of Fah−/−Nod/Scid mice livers by human hepatocytes - BaoLiang Su; ChangCheng Liu; Dao Xiang; HaiBin Zhang; SiMing Yuan; MinJun Wang; Fei Chen; HaiYing Zhu; ZhiYing He; Xin Wang; YiPing Hu (Science China Life Sciences, 2011)

Xeno-repopulation of Fah−/−Nod/Scid mice livers by human hepatocytes - BaoLiang Su; ChangCheng Liu; Dao Xiang; HaiBin Zhang; SiMing Yuan; MinJun Wang; Fei Chen; HaiYing Zhu; ZhiYing He; Xin Wang; YiPing Hu (Science China Life Sciences, 2011)

The Role of β20–β21 Loop Structure in Insecticidal Activity of Cry1Ac Toxin from Bacillus thuringiensis - Yuan Lv; Ying Tang; Yunlei Zhang; Liqiu Xia; Faxiang Wang; Xuezhi Ding; Siming Yi; Wenping Li; Jia Yin (Current Microbiology, 2011)

GIS-based earthquake-triggered landslide hazard zoning using contributing weight model - Meng Wang; Jianping Qiao; Siming He (Journal of Mountain Science, 2010)